PERBEDAAN RERATA PENINGKATAN BERAT BADAN BAYI ANTARA IBU MENYUSUI OBESITAS DAN NORMAL - Desriati Sinaga (STIKes Santa Elisabeth Medan, 2019)
Obesity is one of the trigger factors for the incidence of non-communicable diseases as well as increasing morbidity in mothers and infants. Obesity experienced by mothers before pregnancy can affect the increase in baby's weight. Goals : Analyze differences in the increase in infant weight of obese and normal breastfeeding mothers. Method : Observational study with cross sectional design for 40 breastfeeding mothers and their babies in the work area of Andalas Community Health Center, Ikur Koto Health Center and Lubuk Buaya Health Center in Padang City with consecutive sampling techniques from August to November 2017. Increased body weight was obtained from a 1-month baby weight reduction with baby's birth weight. Data analysis using independent t test to see the difference between the two groups of variables. Result : There was a difference in the increase in infant weight from obese mothers with normal breastfeeding mothers (p = 0.023).Conclusion : Lower weight gain in infants of obese mothers. It is recommended for breasfreeding mothers, especially obese mothers, to continue to give exclusive breastfeeding and not to give formula milk or other foods even though the baby's weight gain was slow.